The Impact of Bureaucracy Delayering Policy on Government Employees: Insights from Eastern Indonesia's Vertical Institutions - Pradana, I Putu Yoga Bumi; Wijayanti, Nadia Sasmita; Rijoly, Jacobus Cliff Diky (Universitas Teuku Umar, 2024)
This article explores the impact of top-down delayering policies on government employees in vertical institutions in Eastern Indonesia. This study used a qualitative approach through in-depth interviews with government employees in three vertical agencies in East Nusa Tenggara. Four main dimensions are explained: job suitability with competencies, future career patterns, innovative work behavior, and employee welfare. Findings indicate a significant mismatch betsween employee competencies and the demands of the new position, resulting in decreased efficiency, role confusion, and low morale. Concerns about unclear future career patterns were also identified, affecting employee motivation and morale. On the other hand, the transition to a more functional structure contributes to an increase in innovative work behavior, with employees feeling more empowered to make creative contributions. Apart from that, this policy also positively impacts the economic welfare of employees through increasing benefits and performance. This research underscores the importance of effective change management, adequate preparation, and communication in implementing bureaucratic delayering policies. Limitations of the study include the limited sample and focus on individual perceptions.